Development of the Payment System in Uzbekistan - Babaeva Guzal Yashinovna; Khakimova Dilnoza Akmalovna (Periodica Journal, 2022)
The article considers the structure of the country's payment system, gives a description of its constituent elements and an overview analysis of their functioning.
Keywords: Payment system; Interbank payment system; Clearing settlement system of the Central Bank; Instant payment system